2002
DOI: 10.1042/cs1030451
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicron-remnant-like particles inhibit receptor-mediated endothelium-dependent vasorelaxation in pig coronary arteries

Abstract: The influence of native and oxidized chylomicron-remnant-like particles (CMR-LPs) on endothelium-dependent relaxation in pig coronary arteries was studied. Artificial lipid particles of a size and lipid composition resembling chylomicron remnants and containing pig apolipoprotein E were used to investigate the effects of chylomicron remnants on the relaxation of isolated segments of pig coronary arteries in response to three endothelium dilators: 5-hydroxytryptamine (5-HT), bradykinin and the calcium ionophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…In contrast, the early PGI 2 release observed in remnant-stimulated cells was not affected by NS-398 treatment and is probably mediated through COX-1 activation. eNOS expression was not modified by CMR-LP treatment, indicating that changes in enzyme expression are unlikely to account for the remnantmediated decrease in basal cGMP observed in the present study, or in previous studies in whole vessels [3,8,10]. Exposure of HUVECs to CMR-LPs caused a rapid activation of the ERK1/2 family of mitogen-activated protein kinases, whose activation has been implicated in regulating COX-2 expression.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In contrast, the early PGI 2 release observed in remnant-stimulated cells was not affected by NS-398 treatment and is probably mediated through COX-1 activation. eNOS expression was not modified by CMR-LP treatment, indicating that changes in enzyme expression are unlikely to account for the remnantmediated decrease in basal cGMP observed in the present study, or in previous studies in whole vessels [3,8,10]. Exposure of HUVECs to CMR-LPs caused a rapid activation of the ERK1/2 family of mitogen-activated protein kinases, whose activation has been implicated in regulating COX-2 expression.…”
Section: Discussioncontrasting
confidence: 65%
“…Briefly, a lipid mixture (50 mg) comprising 70% (w/w) trilinolein, 25% (w/w) phospholipid, 3% (w/w) cholesteryl oleate and 2% (w/w) cholesterol in 0.9% NaCl in Tricine buffer (20 mM, pH 7.4) was emulsified by sonication, and apolipoprotein E (ApoE) was transferred from human serum on to the appropriately sized particles [10]. The CMR-LPs resembled physiological CMRs in size, density and lipid composition, and had triacylglycerol/total cholesterol ratios of (4.01 ± 0.76):1 (n = 19 preparations).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size, density and lipid composition of the CRLPs used was similar to that of physiological remnants [40,41], and they also contained human apoE. Extensive previous studies in both humans and experimental animals have shown that model particles of this type are cleared from the blood and metabolized in a similar way to the corresponding physiological lipoproteins [42–45], and CRLPs containing apoE from the appropriate species have also been found to have effects which mimic those of physiological remnants in rat hepatocytes and pig endothelial cells [40,46–48]. As lipophilic antioxidants can easily be incorporated into the model particles, CRLPs provide a suitable and convenient model for our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacological studies in rat and porcine vessels have now shown that CRLPs inhibit relaxation and potentiate vasoconstriction in an endothelium-dependent manner which is mediated, at least partly, by impaired generation of the vasodilator molecule NO (nitric oxide) [6,7]. Evidence that these particles also reduce basal NO production by cultured porcine ECs was subsequently provided [8].…”
Section: Cmrs (Chylomicron Remnants) and The Vessel Wallmentioning
confidence: 97%